2022
DOI: 10.1021/acs.inorgchem.1c03805
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Crystal Structure Formation and Optical Properties within the Ag–BII–MIV–X (BII = Sr, Pb; MIV = Si, Ge, Sn; X = S, Se) Family of Semiconductors

Abstract: showing that each takes on the noncentrosymmetric cubic space group I4̅ 3d and is isostructural to the previously reported compound Ag 2 Sr 3 Ge 2 Se 8 . Through hybrid density functional theory calculations, these cubic compounds are demonstrated to be (quasi-)direct band gap semiconductors with high densities of states at the band maxima. The band-gap energies are measured by reflectance spectroscopy as 1.95(3) and 2.66(4) eV for Ag 2 Pb 3 Si 2 S 8 and Ag 2 Sr 3 Sn 2 S 8 , respectively. We further measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…3b). It is comparable with the band gaps of recently developed Pb-containing chalcogenide IR NLO materials such as Pb 2 P 2 S 6 (2.6 eV), 65 Pb 4 SeBr 6 (2.62 eV), 66 and PbGa 2 GeS 6 (2.64 eV), 67 and larger than those of α-Pb 2 GeSe 4 (1.42 eV), 68 Sr 0.25 Pb 1.75 GeSe 4 (1.48 eV), 68 Sr 1.3 Pb 0.7 GeSe 4 (1.65 eV), 68 Pb 0.72 Mn 2.84 Ga 2.95 Se 8 (1.65 eV), 69 Pb 4 Ga 4 GeSe 12 (1.91 eV), 70 Ag 2 Pb 3 Si 2 S 8 (1.95 eV), 71 PbGa 2 GeSe 6 (1.96 eV), 72 PbSnSiS 4 (2 eV), 73 Pb 3 SBrI 3 (2.16 eV), 74 Pb 5 Ga 6 ZnS 15 (2.32 eV), 75 β-PbGa 2 S 4 (2.46 eV), 76 and Li 2 PbSiS 4 (2.51 eV). 77 Usually, the LIDT is proportional to the band gap, thermal conductivity, and the sample quality.…”
Section: Resultsmentioning
confidence: 99%
“…3b). It is comparable with the band gaps of recently developed Pb-containing chalcogenide IR NLO materials such as Pb 2 P 2 S 6 (2.6 eV), 65 Pb 4 SeBr 6 (2.62 eV), 66 and PbGa 2 GeS 6 (2.64 eV), 67 and larger than those of α-Pb 2 GeSe 4 (1.42 eV), 68 Sr 0.25 Pb 1.75 GeSe 4 (1.48 eV), 68 Sr 1.3 Pb 0.7 GeSe 4 (1.65 eV), 68 Pb 0.72 Mn 2.84 Ga 2.95 Se 8 (1.65 eV), 69 Pb 4 Ga 4 GeSe 12 (1.91 eV), 70 Ag 2 Pb 3 Si 2 S 8 (1.95 eV), 71 PbGa 2 GeSe 6 (1.96 eV), 72 PbSnSiS 4 (2 eV), 73 Pb 3 SBrI 3 (2.16 eV), 74 Pb 5 Ga 6 ZnS 15 (2.32 eV), 75 β-PbGa 2 S 4 (2.46 eV), 76 and Li 2 PbSiS 4 (2.51 eV). 77 Usually, the LIDT is proportional to the band gap, thermal conductivity, and the sample quality.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, for the Ag-containing cubic chalcogenides Ag 2 Pb 3 Si 2 S 8 , Ag 2 Sr 3 Sn 2 S 8 , Ag 2 Sr 3 Si 2 S 8 , Ag 2 Sr 3 Ge 2 S 8 , and Ag 2 Sr 3 Ge 2 Se 8 , we found that experimental DRS band gap estimates are smaller than the computationally predicted gaps from DFT-HSE06+SOC (ω = 0.2 Å –1 and α = 0.25) by 0.1–0.3 eV. Given this range of observations and understanding of the uncertainty involved, we have therefore employed ω = 0.2 Å –1 and α = 0.25 as a uniform standard for band structure computations in our past work. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…All calculations in this work utilize FHI-aims, a high-precision, , all-electron code using numeric atom-centered basis functions for numerical discretization of orbitals and densities. A linear-scaling approach to evaluate hybrid density functionals is included in FHI-aims. , The general approaches and technical choices made in the work reported here reflect the experience gained from our previous work on multinary chalcogenide semiconductors. ,,, According to Hund’s rules, the Eu 2+ ion has all seven 4f orbitals filled with a single electron each in a high-spin configuration. Therefore, the initial moment of Eu is set as seven to represent the net spin moment of the Eu 2+ ion, and all simulations include spin polarization to reflect the spin of Eu 2+ .…”
Section: Methodsmentioning
confidence: 99%
“…Vacancy disorder for the two Ag sites in the structures of II, III and IV were modelled as described previously for this structure type. 47 Next, spin-polarized densities-of-states (DOS) calculations were performed using an 8 × 8 × 8 k-point mesh (total: 75 k-points) for I and 4 × 4 × 4 k-point meshes (total: 36 k-points) for II to IV. An effective on-site Coulomb interaction for the Eu 4f orbitals was approximated at 6 eV, consistent with prior literature.…”
Section: Second Harmonic Generation (Shg)mentioning
confidence: 99%